Makalah Analisis Ekspansi Samsung Electronics di Vietnam (SEV): Perspektif Foreign Direct Investment (FDI), Motif Ekspansi Internasional, dan Dampak Ekonomi terhadap Negara Tujuan - Wahyu Ari Febriyati; Daspar, S.E,M.M Daspar, S.E,M.M (CV. ITTC INDONESIA, 2026)
Multinational corporations play an important role in promoting economic globalization through cross-border business expansion and investment. One prominent example is Samsung Electronics, which has established Vietnam as one of its major manufacturing hubs in Asia. This study aims to analyze the motives behind Samsung Electronics’ expansion into Vietnam, examine the implementation of Foreign Direct Investment (FDI) based on the Ownership–Location–Internalization (OLI) paradigm, and evaluate its economic impact on Vietnam as the host country. The research employs a qualitative approach using a literature review method by analyzing relevant academic journals, books, and official reports. The findings indicate that Samsung’s investment decision was driven by Vietnam’s location advantages, including competitive labor costs, supportive government policies, and well-developed industrial zones. The investment has generated significant positive impacts, such as job creation, technology transfer, enhanced manufacturing capacity, and increased national exports. However, it has also presented challenges, including dependence on foreign investment, competition with domestic industries, and the need to improve workforce skills to support high-technology manufacturing. Therefore, stronger collaboration between the government and the private sector is essential to ensure that the long-term benefits of foreign investment contribute sustainably to national economic development.